Participatory modelling for stakeholder involvement in the development of flood risk management intervention options. (August 2016) - Maskrey, Shaun A.; Mount, Nick J.; Thorne, Colin R.; Dryden, Ian
Abstract: Advancing stakeholder participation beyond consultation offers a range of benefits for local flood risk management, particularly as responsibilities are increasingly devolved to local levels. This paper details the design and implementation of a participatory approach to identify intervention options for managing local flood risk. Within this approach, Bayesian networks were used to generate a conceptual model of the local flood risk system, with a particular focus on how different interventions might achieve each of nine participant objectives. The model was co-constructed by flood risk experts and local stakeholders. The study employs a novel evaluative framework, examining both the process and its outcomes (short-term substantive and longer-term social benefits). It concludes that participatory modelling techniques can facilitate the identification of intervention options by a wide range of stakeholders, and prioritise a subset for further investigation. They can help support a broader move towards active stakeholder participation in local flood risk management. Highlights: Case study uses participatory modelling approach to involve local stakeholders. Application of Bayesian networks to co-construct conceptual model of flood risk. Testing of model with stakeholders to identify recommended interventions. Approach evaluated using five requirements specific to flood risk management. Approach effective at identifying interventions that merit further exploration.